Photodynamic Therapy: A Distinctive Spinach‐Based Carbon Nanomaterial with Chlorophyll‐Rich and Near‐Infrared Emission for Simultaneous In Vivo Biothiol Imaging and Dual‐Enhanced Photodynamic Therapy of Tumor (Adv. Therap. 7/2019). Issue 7 (8th July 2019) - Liu, Rongjun; Zhang, Liangliang; Zhao, Jingjin; Hou, Cheng; Huang, Yong; Huang, Zirong; Zhao, Shulin
Abstract : In article number1900011, Liangliang Zhang, Shulin Zhao and co‐workers synthesize a chlorophyll‐rich biomass quantum dots‐Cu 2+ nanocomposite, and use it as a distinctive fluorescence nanoprobe and highly efficient photosensitizer for simultaneous fluorescence imaging and dual enhanced photodynamic therapy of tumors. This work allows photosensitizers to be used in tumor recognition, enabling the integration of tumor diagnosis and dual‐enhanced photodynamic therapy.